Analysis of Factors Causing Bad Debts and Efforts to Overcome and Resolve Bad Debts - Septiandra Loviriani; Lili Syafitri; Aris Munandar (ProBisnis : Jurnal Manajemen, 2023)
CV. Jakaharta Palembang is a distributor company of household supplies which in its business activities sells products, such as: stella, hit, mitu, glue mouse stamp elephant, fogo, proclin, carrera sponge and others. The payment system for purchasing goods at CV. Jakaharta Palembang can be done in cash or credit. The existence of a credit system sale gives rise to accounts receivable and bad debts. The purpose of this study was to determine the factors that cause bad debts and efforts to overcome and resolve bad debts at CV. Jakaharta Palembang. The following are the results of research on the factors that cause bad debts at CV Jakaharta Palembang from internal and external parties. From internal parties, such as: not yet implementing a payment system in installments or in installments, not yet applied grouping based on the age of accounts receivable and weak collection techniques. While external factors, such as: bad character, declining financial conditions and failure of the business they operate. Efforts to overcome bad debts that have been made by CV. Jakaharta Palembang by visiting the store, finding solutions and making a warning letter. While the efforts to resolve bad debts that have been made by CV. Jakaharta Palembang by rescheduling and reconditioning. For future research, it is suggested that in order to reduce bad debts above 3% at CV. Jakaharta Palembang, it can be done by applying payments in installments, hiring debcollectors and providing discounts who want to pay off their debts